Association between magnesium and vitamin D status in adults with high prevalence of vitamin D deficiency and insufficiency - Zittermann, Armin; Zelzer, Sieglinde; Herrmann, Markus; Kleber, Marcus E.; März, Winfried; Pilz, Stefan (European journal of nutrition, 2025)
Purpose It has been assumed that magnesium (Mg) status may interact with vitamin D status. We therefore aimed at investigating the association between Mg and vitamin D status in a large cohort of adult individuals with a high prevalence of deficient/insufficient vitamin D and Mg status. Methods We used data from the Ludwigshafen Risk and Cardiovascular Health Study (n = 2,286) to analyze differences according to serum Mg status in circulating 25-hydroxyvitamin D [25(OH)D] (primary endpoint), 24,25-dihydroxyvitamin D3 [24,25(OH)2D3], vitamin D metabolite ratio and calcitriol, and odds ratios for deficient or insufficient 25(OH)D (secondary endpoints). We performed unadjusted and risk score (RS) adjusted and matched analyses. Results Of the study cohort (average age > 60 years), one third was 25(OH)D deficient (< 12 ng/mL), one third 25(OH)D insufficient (12 to < 20 ng/mL), about 10% Mg deficient (< 0.75 mmol/L) and additional 40% potentially Mg deficient (0.75 to 0.85 mmol/L). In adjusted/matched analyses, 25(OH)D was only non-significantly lower in Mg deficient or insufficient groups versus their respective control group (P > 0.05). Only the RS-adjusted, but not the RS-matched odds ratio of 25(OH)D deficiency was significantly lower for the group with adequate versus deficient/potentially deficient Mg status (0.83; 95%CI: 0.69-0.99), and only the RS-matched, but not the RS-adjusted odds ratio of 25(OH)D insufficiency was significantly lower for non-deficient versus deficient Mg status (0.69; 95%CI: 0.48-0.99). Other adjusted or matched secondary endpoints did not differ significantly between subgroups of Mg status. Conclusions Our data indicate only little effect between Mg and vitamin D status in adults with high prevalence of vitamin D deficiency and insufficiency.